The eccentric-distance sum of some graphs - Padmapriya P; Veena Mathad (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2017)
Let G = (V,E) be a simple connected graph. Theeccentric-distance sum of G is defined asξ^ds(G) =_{u,v}V(G) [e(u)+e(v)] d(u,v), where e(u) %the eccentricity of the vertex u in G and d(u,v) is thedistance between u and v. In this paper, we establish formulaeto calculate the eccentric-distance sum for some graphs, namelywheel, star, broom, lollipop, double star, friendship, multi-stargraph and the join of P_n-2 and P_2.